Cumplimiento de indicadores de calidad en el área de Medicina Interna del Hospital Isidro Ayora - Curimilma Chuquimarca, Eliana de los Angeles (2023)
Patient safety is currently of great importance for both facilities and health professionals, who must be prepared to provide quality care in accordance with the protocols of the Ministry of Public Health. The objective of this research was to evaluate compliance with quality indicators in the Internal Medicine Area at the Isidro Ayora Hospital in the city of Loja; the study methodology is non-experimental-observational, with a quantitative, descriptive, and cross-sectional approach. For data collection, the technique of documentary review and direct observation was used, supported by an observational list characterized by having two sections, the first one the characterization of the service, and the second segment evaluated the compliance with safe practices which presented a scale of (YES COMPLIANCE) and (NO COMPLIANCE). The results found in the Internal Medicine service show that the total compliance of the administrative practices is 75% and 25% which do not comply; the assistance practices had a compliance of 56% and 44% did not comply with the indicators and the administrative/assistance practices had a compliance of 60% and 40% which did not comply with the indicators of the safe practices. Once the corresponding analysis was carried out based on the data obtained, it was concluded that there is a high percentage of quality and total safety that the nursing staff provides to the patients, since the staff provides their service and total help to the full improvement of the user with their knowledge and skills